Análisis de minimización de costos de infusiones endovenosas aplicadas en pacientes hospitalizados y pacientes ambulatorios en el servicio de reumatología en un hospital de Lima, Perú - Gallegos Vergara, Clara (2015)
Objective: To measure the costs of therapy hospital intravenous infusion. vs outpatient service of Rheumatology, the National Hospital Edgardo Rebagilati Martins (HNERM) in Lima Peru, in 2009. Methods: The study design was a descriptive, retrospective and transversal. The population was comprised of all hospitalized patients (N =42) who received intravenous infusions of rituximab, pamidronate, infliximab, abatacept, tocilizumab, zoledronic acid and cyclophosphamide in the service of Rheumatology. Inclusion criteria were to be of both sexes over thirteen policyholders and / or beneficiaries of EsSalud. Medical and non-medical direct costs are for one year. A chip was developed, in which socioeconomic and demographic information requested type. The marginal costs of the alternatives were identified. Results: The study population was characterized by a greater proportion of female university level higher education, and prevalence of rheumatic diseases in the age group of 42-52 years and up. The total annual cost of hospitalization amounted to S / 472 726,21 (US $ 166 160,355); and for outpatient alternative to S / 416 092,25 (US $ 146 253,867), which make a difference in S / 56 633,96 (US $ 19 906,49) is equivalent to 12% savings. The management of outpatient intravenous infusions (in policyholders who have no hospitalization criteria) allowed reduce costs arising from hospitalization (hotel, food and staff). The biggest difference in this study was established hospitality costs (day bed), personnel costs and cost of lost productivity. Conclusions: The administration of intravenous infusions outpatients had lower costs for the institution and for the insured, thus optimizing resources.